On the chromatic index of generalized truncations - Alspach, Brian (Ars mathematica contemporanea, 2022)
We examine the chromatic index of generalized truncations of graphs and multigraphs. The insertion graphs considered are complete graphs, cycles, regular graphs and forests.
Keywords: chromatic index; generalized truncation; kromatski indeks; posplošena trunkacija